Scaffolding Structural Thinking in Critical Reading: A Quasi-Experimental Study on CTL-Based Liveworksheets for Popular Scientific Text - Nurrahmah, Faiza; Afnita, Afnita (Jurnal Pendidikan Progresif, 2025)
Scaffolding Structural Thinking in Critical Reading: A Quasi-Experimental Study on CTL-Based Liveworksheets for Popular Scientific Text. Objective: Students' reading skills in Indonesia remain low, as evidenced by the 2022 PISA scores, partly due to the limitations of static print media in facilitating critical thinking required by the Merdeka Curriculum. This study aims to determine the effectiveness of interactive digital Liveworksheets based on Contextual Teaching and Learning (CTL) compared to printed worksheets in improving Grade VIII students' critical reading skills on popular scientific articles. Methods: This study employed a quantitative, quasi-experimental, posttest-only control-group design. The sample consisted of 68 eighth-grade students at SMP Negeri 1 Padang, selected via cluster random sampling and divided into an experimental class (N=34) using CTL-based Liveworksheets and a control class (N=34) using printed worksheets. Data were collected using a validated objective test (30 items, Alpha 0.878) measuring text content, structure, and linguistic features, combined with a qualitative analysis of students' written responses to assess cognitive engagement. Data analysis included descriptive statistics, normality and homogeneity tests, an independent samples t-test, and Cohen’s d effect size calculation. Findings: The results indicated a significant difference in learning outcomes. The experimental class achieved a higher mean score (88.04) compared to the control class (83.04). The t-test confirmed this significance with a p-value of 0.046 (p < 0.05). Furthermore, the effect size calculation (d=0.49) indicated a moderate practical impact. Specifically, the experimental group demonstrated superior performance in analyzing text structure compared to the control group. Conclusion: The integration of CTL components, specifically modeling and constructivism, within the interactive features of Liveworksheets proved effective in enhancing students' reading competencies. Therefore, this media serves as a viable alternative to support digital literacy and critical reading instruction in secondary schools.        Keywords: critical reading skills, liveworksheets, contextual teaching and learning, popular scientific articles, digital literacy.